Croatian film as a medium of memory of the Yugoslav wars of the 1990s - Boguska, Anna (Balcanica Posnaniensia. Acta et studia, 2024)
The article is an attempt to present selected Croatian new war films as media of memory of the war of the 1990s in the countries of the former Yugoslavia. The authoress is primarily interested in the narrative structure of the presented forms of mediated memory. In the three analysed films, a medium of memory is identified as: ideological (Madonna, Neven Hitrec, 1999), mimetic (Witnesses, Vinko Brešan, 2003), and poietic (The Living and the Dead, Kristijan Milić, 2007), which allows her to draw conclusions about the heterogeneous, dialectical nature of the corpus of Croatian new war films.